Effect of Material Behavior on Dynamic Characteristics Determination of Marine Propeller Blade Using Finite Element Analysis. (2016) - Kishore, M.L. Pavan; Behera, R.K.; Pradhan, S.K.; Parida, P.K.
Abstract: Natural frequency tuning is a vital problem in engineering. Every structure possesses its natural frequencies where vibrational loading at nearby frequencies excite the structure. This causes the structure to oscillate until energy is dissipated through friction or structural failure. A classical aspect of good structural design lies in optimising the stiffness to mass ratio through material, and shape. It may appear that natural frequencies can be manipulated as an afterthought. For more conventional structures, however, the roles of material, cross-section and boundary conditions are all comparatively small in allowing frequencies. This study of proposed work mainly focuses on the effect of material on the dynamic characteristics behaviour of marine propeller. Using appropriate finite element modelling desired simulation of the structure can be achieved to ensure a certain level of safety.